Pemberdayaan Wali Santri melalui Usaha Brownis di Pondok Pesantren Hidayatul Mubtadi’in Wedi Kapas Bojonegoro - Sa'diyin, Moh.; Afan Zaini, Ahmad; Muhyidin, Muhyidin; Hidayatur Rohmah, Nurul (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Sware of their potential, then the potential or assets need to be developed. This assistance is carried out in an effort to make the potential of the guardians of PP Hidayatul Mubtadi'in students more optimal. This assistance is manifested in the form of empowerment, the target of this empowerment is the guardians of students and caregivers, so that their potential can have a positive impact on the guardians of students and Islamic boarding schools in the economic sphere to become more established and prosperous. Empowerment is carried out using the ABCD (Asset base community development) method using several stages, including: Inculturation; Discovery; Dreams; Design; Define; and Destiny. The steps taken in empowering santri guardians in improving the economy, namely: brownies making training activities. This empowerment is implemented in activity 1, activity 2, and activity 3. With this training program, guardians of students and caregivers will be motivated to be more innovative in taking advantage of opportunities and assets they have and be encouraged to develop creative assets within themselves so that the economy of families and Islamic boarding schools is further improved. for a more prosperous future